2001
DOI: 10.1034/j.1600-0420.2001.790518.x
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus surgery: Fibrin glue versus vicryl for conjunctival closure

Abstract: ABSTRACT.Purpose: The aim of present study was to compare the results of conjunctival closure by fibrin glue with vicryl in strabismus surgery. Methods: 19 patients undergoing bilateral symmetrical strabismus surgery were included in this study. Conjunctival incisions were closed with 6-0 vicryl in the right eye and fibrin glue in the left eye. Results: On first post-operative day 15 out of 19 eyes (78.9%) had well apposed conjunctiva, 3 out of 19 eyes (15.79%) had 1 mm retraction and one out of 19 eyes (5.26%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 9 publications
2
17
1
1
Order By: Relevance
“…We might speculate that this technique may be less effective on the lateral side of the eye than the medial side because of the difference in width of these two areas. Dadeya and Ms (2001) applied fibrin sealant in the same way and observed that conjunctival closure with Vicryl sutures resulted in increased discomfort and inflammation during the early postoperative period compared with fibrin sealant. They observed that none of the eyes in which fibrin sealant was applied had ocular discomfort as compared to 8 out of 19 (42.1%) eyes in which 6-0 vicryl was used for conjunctival closure.…”
Section: Discussionmentioning
confidence: 94%
“…We might speculate that this technique may be less effective on the lateral side of the eye than the medial side because of the difference in width of these two areas. Dadeya and Ms (2001) applied fibrin sealant in the same way and observed that conjunctival closure with Vicryl sutures resulted in increased discomfort and inflammation during the early postoperative period compared with fibrin sealant. They observed that none of the eyes in which fibrin sealant was applied had ocular discomfort as compared to 8 out of 19 (42.1%) eyes in which 6-0 vicryl was used for conjunctival closure.…”
Section: Discussionmentioning
confidence: 94%
“…There is thus a need for an alternative to the use of sutures in surgical procedures involving the eye surface. The use of organic glues has provided good results for the repair of leaking blebs 11,12 and perforated corneal ulcers, 13 conjunctival closure in strabismus surgery, 14,15 surgery for retinal detachment, cataract surgery, 16 trabeculectomy, 17 and mucous membrane grafting to repair lesions of the conjunctival fornix. 18 In conjunctival autograft surgery of the pterygium itself, there have been successful reports of fixing the graft to the episclera using a fibrin glue to minimize sutures 7 as well as the use of this adhesive to completely avoid sutures.…”
Section: Discussionmentioning
confidence: 98%
“…Dadeya and Kamlesh also compared discomfort of vicryl sutures and fibrin sealant for conjunctival wound closure. No cases in which fibrin sealant was used experienced postoperative discomfort while discomfort was reported for 42% of the eyes closed with vicryl sutures [79].…”
Section: Strabismus Surgerymentioning
confidence: 97%